Review of Screen Channel Liquid Acquisition Device for Cryogenic Propellants - Ma Yuan; Chen Hong; Xing Kewei; Wang Lei; Li Yanzhong (Zhileng xuebao)
In an effort to mitigate the difficulty of acquisition and transfer of liquid propellant in space systems, existing in-space gas-liquid separation techniques for cryogenic propellants are evaluated. In particular, the theoretical knowledge and experimental results of screen channel liquid acquisition devices (LADs) are investigated from the vantage point of three aspects—bubble point, pressure drop, and performance optimization. The following conclusions can be drawn: 1) The bubble point is generally higher for finer screens; however, as the density of the mesh increases, the bubble point of the 510 × 3600 Dutch Twill (DT) screen becomes lower than that of the DT-450 × 2750 screen; 2) Compared to ground conditions, the pressure drop of the screen channel LAD is much lower and mainly governed by the flow-through-screen pressure drop under microgravity, which corresponds to a higher critical mass flow rate and could meet the requirement of higher delivery mass flow rate; 3) Reducing the fluid temperature and using a non-condensable gas (such as helium) to pressurize the tank could enhance the screen bubble point and improve the separation performance of screen channel LAD; 4) The DT-450×2750 screen might be a preferential weave for future liquid hydrogen fuel depots, because it could simultaneously meet the requirement of high bubble point and high critical mass flux.